Human Resources (HR) Productivity in Access Infrastructure (Sub-Division) to Succeed Digital Era (Case Study PT. Telekomunikasi Division of Telekomunikasi Regional III West Java) (The Indonesian Journal of Business Administration, 2021)
PT. Telekomunikasi Indonesia prepares Human Resources who have broad insight (global mindset) as well as those who have special criteria including being able to interact with business partners, humble and able to adapt to the business environment. The problem in this research is the limited number of employees in the Infra Access section of the Regional III West Java. There is also an imbalance between the number of recruits for fresh graduates and the number of employees who leave (retired). With this case there will be a negative impact on the achievement of business/production targets at the company. With these problems, the researcher explores matters relating to employees as the most important organizational asset owned by the company. This study analyzes the things that affect employee productivity, employee innovation and how the network management function in the company reaches the customer properly and smoothly. This research method uses a SWOT analysis method that produces a TOWS matrix, namely SO, WO, ST and WT. This study also uses a qualitative descriptive method by collecting interview and observation data. Interviews were conducted with internal stakeholders of PT. Telecommunications Division Telkom Regional III West Java, which includes elements of Human Capital, Finance, Infra Access Network and personnel who are directly involved with employees who create innovations. The results of the study show that the company's targets can be achieved and increase every year. This is analyzed from financial data for three consecutive years from 2018 to 2020. The results of work productivity and employee creativity & innovation are also able to make breakthroughs and applications that simplify customer service on the internet, IndiHome, IPTV etc. Keywords: Access Infrastructure, Work Productivity, Innovation, Telecommunication